ZLM-7 Blocks Breast Cancer Progression by Inhibiting MDM2 via Upregulation of 14-3-3 Sigma - Min Wen; Zi-Zheng Zou; Tiao Luo; Xuan Li; Su-You Liu; Ji-Jia Li; Zhi-Yong Luo (MDPI AG, 2022)
Breast cancer is one of the most prevalent malignancies with poor prognosis. Inhibition of angiogenesis is becoming a valid and evident therapeutic strategy to treat cancer. Recent studies uncovered the antiangiogenic activity of ZLM-7 (a combretastain A-4 derivative), but the regulatory mechanism is unclear. ZLM-7 treatment was applied in estrogen receptor-positive cell MCF-7, triple-negative breast cancer cell MDA-MB-231 and xenograft models. Transfections were conducted to overexpress or knockdown targeted genes. The gene and protein expressions were measured by qPCR and Western blotting assay, respectively. Cell proliferation and apoptosis were evaluated using the CCK8 method, clone formation assay and flow cytometry. We found that ZLM-7 upregulated 14-3-3 sigma expression but downregulated MDM2 expression in breast cancer cells. ZLM-7 delayed cell proliferation, promoted apoptosis and blocked cell-cycle progression in human breast cancer cells in vitro, while those effects were abolished by 14-3-3 sigma knockdown; overexpression of 14-3-3 sigma reproduced the actions of ZLM-7 on the cell cycle, which could be reversed by MDM2 overexpression. In xenograft models, ZLM-7 treatment significantly inhibited tumor growth while the inhibition was attenuated when 14-3-3 sigma was silenced. Collectively, ZLM-7 could inhibit MDM2 via upregulating 14-3-3 sigma expression, thereby blocking the breast cancer progression.